Developing development: creating a practical program - Doty, Noelle Christine (Kansas State University, 2019)
In the constantly changing organization, effective learning within the workplace offers organizational members opportunities to grow and adapt to those changes. To understand the process of effective learning in organizations, this report distinguishes the area of onboarding from the area of employee development training by reviewing theory and descriptive literature, followed by identifying prescriptive principles based on that literature, and finally, providing an exemplar for practice. This report opens by utilizing leader-member exchange theory (LMX) to set the foundation for leadership in learning. Once the frame of LMX is established, organizational socialization theory informs the discussion of onboarding, and elements of adult learning informs the process of employee development training. Also provided is a discussion of future directions for research, theory, and practice.
Keywords: Training & Development; Socialization; Onboarding; Adult Learning